NOTES for the management of an intra-abdominal abscess: transcolonic peritonoscopy and abscess drainage in a canine model - Moustarah, Fady (Canadian Medical Association, 2013)
BACKGROUND: We studied natural orifice transcolonic drainage of intra-abdominal abscesses in a canine survival model to evaluate the difficulty of peritonoscopy and abscess drainage and the reliability of endoluminal colotomy closure. METHODS: We placed a 7 cm nonsterile saline-filled latex balloon intra-abdominally to mimic or induce an abscess or inflammatory mass. Seven days later, we advanced a single-channel endoscope transanally into the sigmoid colon of the animal, made a colotomy and then advanced the endoscope intraperitoneally. We evacuated the identified abscess and placed a drain transabdominally. We closed the colotomy endoluminally with a tissue approximation system using 2 polypropylene sutures attached to metal T-bars. Two weeks later, we evaluated the colotomy closure at laparotomy. RESULTS: We studied 12 dogs: 8 had subphrenic balloon implants and 4 had inter-bowel loop implants. Eleven survived and underwent transcolonic peritonoscopy; we identified the “abscess” in 9. The colotomy was successfully closed in 10 of 11 dogs. Although abscesses were easily identified, the overall difficulty of the peritonoscopy was moderate to severe. One dog required colotomy closure via laparotomy, while 9 had successful endoluminal closure. After colotomy closure, 8 animals survived for 2 weeks (study end point) without surgical complications, sepsis or localized abdominal infections. On postmortem examination, all closures were intact without any adjacent organ damage or procedure-related complications. CONCLUSION: Natural orifice transluminal endoscopic surgery provides a novel alternative to treating intra-abdominal pathology. It is technically feasible to perform endoscopic transcolonic peritonoscopy and drainage of an intra-abdominal abscess with reliable closure of the colotomy in a canine experimental model.